TECHNOLOGIES FOR WASTEWATER TREATMENT FROM THE FISH PROCESSING INDUSTRY: REUSE ALTERNATIVES - Ribeiro, Fábio Henrique de Melo (2017)
For the fish processing industry, the treatment proposal for effluentsencounters some difficulties, such as high concentration of organic matter andsolids in suspension, and lack of uniformity in the composition. Consideringthis problem, the objective was to evaluate the removal efficiency fordifferent effluent treatment technologies of the mentioned industry andthe possibility of reuse. In order to do so performed a survey of effluenttreatment systems, verifying the removal rate for pH, total suspended solids(TSS mgL-1), biochemical oxygen demand BOD (mgL-1), chemical oxygendemand COD mgL-1), total nitrogen TN (mgL-1), total phosphorus TP (mgL-1)and oils and greases (mgL-1). The concentrations found were compared tothe limit values imposed by the standards for industrial reuse. As a result, ithas been found that the combination of multiple processes, using advancedtreatment techniques, is appropriate, especially where the purpose is toreuse and/or recycle.